Uso de torta de filtro enriquecida com fosfato natural e biofertilizantes em Latossolo Vermelho distrófico - Castellanos González, Leónides; Prado, Renato de Mello [UNESP]; Hernández, Alfredo Reyes; Caione, Gustavo [UNESP]; Parets Selva, Enrique (My University, 2014)
The use of biofertilizers associated with organic compound and phosphate rock can increase the availability of phosphorus in the soil, due to the increase of the microorganisms population. This study aimed at evaluating the effect of filter cake enriched with rock phosphate and biofertilizers preparations on the microorganisms population and phosphorus content of a Haplustox soil. The experiment was conducted in a greenhouse, in a completely randomized experimental design, in a 7×3 factorial scheme (seven treatments and three sampling times), with three replications. Treatments consisted of soil samples with decomposed filter cake and Araxá rock phosphate enriched with microorganisms from the biofertilizers Biopack, Embrafos and Azotofos; soil with filter cake and Araxá rock phosphate not enriched with microorganisms; soil with filter cake; soil with rock phosphate; and single soil (control). The soil phosphorus content and microorganisms population were evaluated at 30, 60 and 90 days after the experiment installation. The use of filter cake enriched with rock phosphate and biofertilizers increased the soil bacteria population, with variations in time. The filter cake also increased the fungi population and phosphate solubilizing microorganisms. In the short term, the addition of filter cake enriched with rock phosphate contributed to the increase of the soil soluble phosphorus content.
Use of filter cake enriched with rock phosphate and biofertilizers in a Haplustox soil
Keywords: Organic residue; Phosphate solubilizing microorganisms; Phosphorus fertilization